2021
DOI: 10.1186/s12985-021-01567-3
|View full text |Cite
|
Sign up to set email alerts
|

Excellent option for mass testing during the SARS-CoV-2 pandemic: painless self-collection and direct RT-qPCR

Abstract: The early identification of asymptomatic yet infectious cases is vital to curb the 2019 coronavirus (COVID-19) pandemic and to control the disease in the post-pandemic era. In this paper, we propose a fast, inexpensive and high-throughput approach using painless nasal-swab self-collection followed by direct RT-qPCR for the sensitive PCR detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This approach was validated in a large prospective cohort study of 1038 subjects, analysed simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Interestingly, patients with high hsCRP levels had shorter survival rates, especially those with a high viral load. The present study suggests the association between patients with either high hsCRP or SAR-CoV-2 viral loads and high mortality due to high viral burden and high inflammation conditions (15)(16)(17)(18) This study adds to this evidence by demonstrating that hsCRP levels at admission possess similar discriminatory ability, suggesting its potential utility as a readily available and cost-effective marker. Most studies that used CRP demonstrated that this test is related to increased mortality rates due to the viral destruction of the vascular injury process.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, patients with high hsCRP levels had shorter survival rates, especially those with a high viral load. The present study suggests the association between patients with either high hsCRP or SAR-CoV-2 viral loads and high mortality due to high viral burden and high inflammation conditions (15)(16)(17)(18) This study adds to this evidence by demonstrating that hsCRP levels at admission possess similar discriminatory ability, suggesting its potential utility as a readily available and cost-effective marker. Most studies that used CRP demonstrated that this test is related to increased mortality rates due to the viral destruction of the vascular injury process.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies to date have looked at the performance of unobserved as well as supervised self-collected specimens for molecular detection of SARS-CoV-2 [ 45 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Thus, Tu and colleagues compared SARS-CoV-2 detection using a variety of swab types self-collected (under health care professional observation) by 530 symptomatic child and adult outpatients (or their parents or guardians), with nasopharyngeal swabs collected by health care professionals as the comparator gold standard [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study has several limitations in terms of interpretation of evidence of superinfection we found in ~10% of analysed samples. Due to the specific features of SARS-CoV-2 RT-qPCR diagnostics [ 28 ] related to extremely high diversity of viral copies in individual samples and a vast number of analysed samples in diagnostic laboratories, contamination of samples cannot be completely excluded. On the other hand, all samples came from accredited and experienced diagnostic laboratories with established laboratory quality control systems (often ISO15189:2013; data available upon request), which ought to minimise the likelihood of accidental contamination.…”
Section: Resultsmentioning
confidence: 99%